Outcome of Per-operative Use of Topical Tranexamic Acid for Reduction of Seroma following Mastectomy in BIRDEM General Hospital, Dhaka, Bangladesh - Imran, Mohammad; Sharmin, Sabrina; Roy, Sharmistha; Mondal, Samiron Kumar (Delta Medical College Journal, 2025)
Background: Formation of a seroma most frequently occurs after mastectomy and axillary surgery. Tranexamic acid is a synthetic antifibrinolytic agent. The role of topical administration of tranexamic acid for reduction of fluid collection in dead space following mastectomy is needed to be evaluated. Objectives: The present study was planned to evaluate the outcome of topical use of tranexamic acid per operatively for reduction of seroma following mastectomy. Materials and method: This prospective observational study was done in BIRDEM General Hospital, Shahbag, Dhaka, Bangladesh, from February 2019 to July 2019. A total of 40 patients of mastectomy were included in the study. Following mastectomy after hemostasis and before wound closure, 1000mg of injection tranexamic acid was sprayed uniformly in the wound (in axilla and under the flaps). Patients were evaluated with complete history, thorough clinical examination and relevant investigations. Collected data were analysed by using SPSS version 23. Results: Out of 40 patients, 9 patients (22.5%) developed seroma and more than two third (66.7%) of which belonged to age group >60 years. Out of which all 9 patients (100%) who were categorized as ASA grade III developed Seroma. Among them, 6 cases developed only seroma and 3 cases had seroma with partial flap necrosis. On 3rd post operative day, all (100%) of the patients in seroma “developed group” had severe pain, whereas only 15(48.4%) in seroma “not developed group” had severe pain. On 5th post operative day, 3(33.0%) patients in seroma “developed group” had severe pain and none in seroma “not developed group”. On 14th post operative day, 6(66.7%) patients were found in mild pain in seroma “developed group” and 3(9.7%) in seroma “not developed group”, that was statistically significant (p<0.05) between two groups. Majority (92.5%) of patients had hospital stay of ≤10 days. The mean hospital stay was found 9.2±1.2 days with range from 8 to 12 days. Conclusion: In conclusion, tranexamic acid is inexpensive. Its cost-effectiveness has been thoroughly documented. Even after operations where bleeding is less common topical application of tranexamic acid may reduce the need for drains and outpatient visits. This simple method has potential for widespread application after surgery. Delta Med Col J. Jul 2022;10(2): 59-65